(untitled) (Nexo Revista Científica, 2021)
The article substantiates the management of the agroresource potential of agricultural landscapes (ARPA) by an integral risk indicator on a digital platform in the Google system to improve the reclamation state of soils. The digital platform for managing the agroresource potential is located in the Hilbert separable space vector field. Management of the agroresource potential proceeds along with a change in the intensity of the energy flow of the substance, which is formed from the use of melioration techniques Energy affects the land reclamation state (LRS) of the agricultural landscape. It has a significant impact on the integral indicators of resource risks. To assess the reclamation state of the agricultural landscape, a critical risk indicator (IIR) has been developed, a resource risk model, which is a simulation and resource model, as it combines various quantitative indicators of LRS with dimensionless risk indicators and determines the critical state of the resource. The base of the computer program contains a resource risk model IIR, which includes risk indicators and the risk safety scale (SSR), which makes it possible to assess the resource potential of the agricultural landscape. The IIR model is adapted to the natural resources of a real agricultural landscape. The basis of the model is the resource risks LRS, with the help of which the management of the reclamation state of the farming landscape is carried out. Optimization of the integral risk indicator for taxa resources reduces the volume of work performed by reclamation techniques.